2012
DOI: 10.1007/s00775-012-0932-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the putative iron ligands in the ferroxidase activity of recombinant human hephaestin

Abstract: Hephaestin is a multicopper ferroxidase expressed mainly in the mammalian small intestine. The ferroxidase activity of hephaestin is thought to play an important role during iron export from intestinal enterocytes and the subsequent iron loading of the blood protein transferrin, which delivers iron to the tissues. Structurally, the ectodomain of hephaestin is predicted to resemble ceruloplasmin, the soluble ferroxidase of blood. In this study, the human hephaestin ectodomain was expressed in baby hamster kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As previously mentioned, HCP1, which is also a ferroxidase, has also an important role during iron export from intestinal enterocytes and its subsequent loading to Tf. Structurally, the ectodomain of HCP1 resemble Cp [90]. …”
Section: Intestinal Iron Exportationmentioning
confidence: 99%
“…As previously mentioned, HCP1, which is also a ferroxidase, has also an important role during iron export from intestinal enterocytes and its subsequent loading to Tf. Structurally, the ectodomain of HCP1 resemble Cp [90]. …”
Section: Intestinal Iron Exportationmentioning
confidence: 99%
“…However, in contrast to ceruloplasmin, hephaestin was incapable of direct oxidation of biogenic amines, such as adrenaline and dopamine [130], implying a difference in biological substrate specificities between these two homologous oxidases. In addition, kinetic studies revealed that similar to ceruloplasmin, hephaestin has two types of iron-binding sites with different affinities towards ferrous iron [131]. Studies involving site-directed mutagenesis confirmed that residues E960 and H965 serve as iron ligands of a high-affinity binding site located in domain 6 of hephaestin [131].…”
Section: Human Multi-copper Oxidasesmentioning
confidence: 99%
“…In addition, kinetic studies revealed that similar to ceruloplasmin, hephaestin has two types of iron-binding sites with different affinities towards ferrous iron [131]. Studies involving site-directed mutagenesis confirmed that residues E960 and H965 serve as iron ligands of a high-affinity binding site located in domain 6 of hephaestin [131]. Based on homology with ceruloplasmin, the remaining ligands of this high-affinity iron-binding site are residues E300 and D996.…”
Section: Human Multi-copper Oxidasesmentioning
confidence: 99%
“…The Type I sites accept electrons from the oxidation of substrate (Fe 2+ to Fe 3+ ), and the electrons from four substrate equivalents are transferred to the trinuclear cluster where they are coupled to the four-electron reduction of O 2 to H 2 O [ 13 ]. Crystal soaking experiments further detailed two ferrous iron binding sites, each in the proximity of one of the Type I copper centers [ 14 ]. Comparative structural modeling has indicated an analogous architecture for HEPH [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative structural modeling has indicated an analogous architecture for HEPH [ 15 ]. However, preparations of recombinant human HEPH expressed in Pichia pastoris or baby hamster kidney (BHK) cells have indicated between 3 and 4 copper ions per HEPH molecule [ 14 , 16 , 17 ]. This discrepancy could indicate that the recombinant production of HEPH leads to incomplete copper loading, or, that HEPH has a different architecture than ceruloplasmin.…”
Section: Introductionmentioning
confidence: 99%